Dietary supplement use among academic pharmacists - Murphy, Michael S. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
United States sales of dietary supplements exceeded $18 billion in 2002, indicating that dietary supplement use is common among the American public. This report describes a survey of academic pharmacists and their use of dietary supplements and herbs. To date, most data comes from retail or community pharmacists, so a survey was developed to collect information regarding dietary supplement and herb usage from academic pharmacists. Academic pharmacists are probably the most knowledgeable group in regards to assessing the clinical value of supplements. Our results showed that 54% of academic pharmacists have used dietary supplements or herbs. However, it is interesting to note that most of the dietary supplements listed were not in the top ten most commonly used supplements. In addition, there was no excessive use of supplements or herbs by this group of pharmacists since the majority of respondents listed multivitamins.